2021
DOI: 10.1038/s41598-021-83464-x
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus phylogeny and historical biogeography of Hypostomus shed light on the processes of fish diversification in La Plata Basin

Abstract: Distribution history of the widespread Neotropical genus Hypostomus was studied to shed light on the processes that shaped species diversity. We inferred a calibrated phylogeny, ancestral habitat preference, ancestral areas distribution, and the history of dispersal and vicariance events of this genus. The phylogenetic and distribution analyses indicate that Hypostomus species inhabiting La Plata Basin do not form a monophyletic clade, suggesting that several unrelated ancestral species colonized this basin in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…I. Montoya-Burgos, 2003;Silva et al, 2016), but contrast with the Oligo-Miocene origin (~25 Ma) proposed recently (Cardoso et al, 2021).…”
Section: Western Amazon Was the Centre Of Origin Of Hypostomusmentioning
confidence: 55%
See 1 more Smart Citation
“…I. Montoya-Burgos, 2003;Silva et al, 2016), but contrast with the Oligo-Miocene origin (~25 Ma) proposed recently (Cardoso et al, 2021).…”
Section: Western Amazon Was the Centre Of Origin Of Hypostomusmentioning
confidence: 55%
“…Deciphering the precise distribution range of a distant ancestor based on its current day descendants depends largely on the completeness of the species sampling, the knowledge of the species distribution range and the size and number of the geographic areas considered in the analysis. Previous attempts to infer the ancestral range of Hypostomus used restricted taxonomic sampling, and resulted in excessively large ancestral distribution range for the first ancestral Hypostomus, encompassing the entire proto Amazon-Orinoco System (Cardoso et al, 2021) or even the proto-Amazon-Orinoco plus Upper Paraná (Silva et al, 2016). With our comprehensive taxonomic sampling of Hypostomus and close relatives, we found that the MRCA of Hypostomus inhabited the Western Amazon, an area that nowadays corresponds to the Upper Amazon Basin including some important tributaries, such as the Madeira, Negro, Purus and Japurá rivers.…”
Section: Western Amazon Was the Centre Of Origin Of Hypostomusmentioning
confidence: 99%
“…However, the use of only this genetic criterion for taxonomic decision has been controversial. In Hypostomus , for example, it was shown that 82% of the sister-species pairs with well-defined morphology, showed genetic divergence values of less than 2% ( Cardoso et al 2019 ; Jardim de Queiroz et al 2020 ; Cardoso et al 2021 ). Despite our genetic results obtaining a distance close to 2% of differentiation, our examination of morphological characters did not find unequivocal characters for the description of a new species.…”
Section: Discussionmentioning
confidence: 99%
“…140 recognized species, the genus Hypostomus Lacépède 1803 (Loricariidae: Hypostominae) is one of the most species‐rich genera within Siluriformes (Froese & Pauly, 2019). Hypostomus species distributions span a broad geographical area from Central America to the southern cone of South America east of the Andes, and the greatest wealth of species in the genus is harboured in the Amazon/Orinoco ecoregion (Cardoso et al ., 2021; Jardim de Queiroz et al ., 2020; Silva et al ., 2016; Zawadzki et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%